Stress appraisals of UK soccer academy coaches: an interpretative phenomenological analysis - Dixon, M.; Turner, M. J. (Qualitative Research in Sport, Exercise and Health, 2018)
Knowledge of how sports coaches appraise stress is sparse. This study investigates coaches` cognitive appraisals and explores the transactional nature of how coaches experience stress. Ten academy soccer coaches were interviewed using a semi-structured guide. Interpretative phenomenological analysis was employed to explore coaches` lived experiences of stressful situations. Coaches identified a range of situational demands including performance expectations, conflicting tasks, and managing relationships. Demands were evaluated in terms of perceived psychological danger. Coaches appraised their ability to meet these demands through resources such as self-efficacy, autonomy and social support. Emotional and behavioural consequences of coaches` cognitive appraisals were also revealed. Findings provide a deeper understanding into the specific cognitive appraisals of coaches, revealing that determinants of stress appraisals are interdependent and complex.